2015
DOI: 10.1007/s00438-015-1102-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of microRNAs and transcript targets related to witches’ broom disease in Paulownia fortunei by high-throughput sequencing and degradome approach

Abstract: Paulownia witches' broom (PaWB) caused by the phytoplasma is a devastating disease of Paulownia trees. It has caused heavy yield losses to Paulownia production worldwide. However, knowledge of the transcriptional and post-transcriptional regulation of gene expression by microRNAs (miRNAs), especially miRNAs responsive to PaWB disease stress, is still rudimentary. In this study, to identify miRNAs and their transcript targets that are responsive to PaWB disease stress, six sequencing libraries were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…These results, together with the results of previous studies, indicate that an integrated co-regulatory network exists in the pathological process of phytoplasma infection [23]. Based on an integrated analysis of the functions of the target genes of the DEMs in this study and the previous ones [23,[51][52][53], we constructed a network that describes the regulation relationship of the DEM-mediated target genes in the manifestation of PaWB symptoms (Figure 3). …”
Section: Genes Involved In Materials Metabolic Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…These results, together with the results of previous studies, indicate that an integrated co-regulatory network exists in the pathological process of phytoplasma infection [23]. Based on an integrated analysis of the functions of the target genes of the DEMs in this study and the previous ones [23,[51][52][53], we constructed a network that describes the regulation relationship of the DEM-mediated target genes in the manifestation of PaWB symptoms (Figure 3). …”
Section: Genes Involved In Materials Metabolic Pathwaysmentioning
confidence: 99%
“…When the same miRNAs were detected in seedlings treated with both reagents, the miRNAs were identified as key miRNAs related to PaWB. Thence, we compared the common DEMs in the three paulownia species with the DEMs detected in our previous studies [23,[51][52][53][54], and found that miR156, miR398, miR408, and miR2118 were common DEMs in the healthy vs. phytoplasma-infected seedling comparisons. Thirdly, to confirm the key miRNAs related to witches' broom, we compared the four identified miRNAs with the miRNAs detected in phytoplasma-infected Mexican lime, Ziziphus jujuba, and mulberry [7, [14][15][16], and found that miR156 was the only common miRNA among the phytoplasma-responsive miRNAs in all these studies.…”
Section: Mir156 Is the Key Regulatory Factor Related To Witches' Broommentioning
confidence: 99%
See 1 more Smart Citation
“…PaWB is caused by phytoplasmas that belong to the Aster Yellows group Candidatus Phytoplasma asteris (16SrI-D) and are spread by insect vectors [4]. PaWB has been the focus of many studies, and some PaWB-related genes [5,6,7,8,9,10], microRNAs (miRNAs) [11,12,13,14], proteins [15,16,17], metabolites [18], and long noncoding RNAs (lncRNAs) [19] have been revealed. However, the underlying mechanisms of PaWB are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…Rifampicin treatment can make PaWB-infected Paulownia recover to normal morphology [13]. Furthermore, the rapid development of 'omics' has allowed for the investigation of the transcriptomes [3,[14][15][16][17][18], microRNAs (miRNAs), degradomes [19][20][21][22], and proteomes [4,23] of Paulownia species, and the results have revealed changes after PaWB infection at transcriptional, post-transcriptional, and translational levels.…”
Section: Introductionmentioning
confidence: 99%